Sri Lankan maternal ancestry reveals early migrations from Africa along the Indian Ocean - Anjana Welikala; Shailesh Desai; Amali Fernando; Joanne Kotelawala; Lakshika Jayasekara; Prajjval Pratap Singh; Anoma Jayasoma; Jose Antonio Urban Aragon; David Witonsky; Niraj Rai; Kumaraswamy Thangaraj; Maanasa Raghavan; et al. (PLoS ONE, 2026)
The African origin of anatomically modern humans is widely accepted. However, there is ongoing debate about the route they took and whether the early expansion into Oceania was through South Asia. Despite Sri Lanka being an island South Asian nation with the earliest known human fossils in South Asia and strategically located along a putative ‘southern route’, a comprehensive examination of its temporal settlement using high-resolution complete mitochondrial DNA analysis has never been conducted. To address this gap, 139 mitogenomes were sequenced in this study from the Sinhalese, Sri Lankan Tamil, and Vedda populations in Sri Lanka and integrated with 247 previously published global mitogenomes, resulting in the largest mitogenome dataset analyzed thus far. Phylogeographic analyses revealed four distinct settlement phases in Sri Lanka, with the earliest phase overlapping with the initial entry of modern humans into South Asia, thus supporting the southern dispersal route. The introduction of West Eurasian lineages into Sri Lanka was mediated via India. A significant decline in effective population size was observed across all studied populations, reflecting the demographic history of the island. Findings from the present study provide valuable insights into the long-standing debate on the southern and inland migration routes out of Africa and subsequent migrations from across Eurasia, thus highlighting the complex settlement patterns of Sri Lanka and broader Asia.